PENGEMBANGAN MEDIA PEMBELAJARAN PAI-BP KELAS VII TERINTEGRASI NILAI-NILAI KEMARITIMAN DI SMP KAWASAN PESISIR - ning, ning mukaromah (Universitas Nahdlatul Ulama Pasuruan, 2024)
The utilization of media in Islamic Education (PAI) learning represents an innovation that teachers can employ to facilitate the transmission and illustration of abstract concepts in a concrete manner to students. The development of PAI and character education media integrates maritime values for seventh-grade students in coastal areas. The maritime values instilled through this learning media encompass courage, perseverance, cooperation, responsibility, navigation skills, environmental sustainability, resilience, and maritime life skills. This study aims to 1) describe the procedure of developing integrated PAI-BP (Islamic Education and Character Education) learning media with maritime values, and 2) delineate the impact of using these learning media products on student learning motivation. The research method utilized is Research and Development (R&D), employing the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Data sources include seventh-grade students from coastal areas (NU Junior High School, Nurul Mushthofa Islamic Junior High School, and Pasir Panjang Wates Junior High School). Data collection instruments consist of questionnaires and observations. The findings reveal that the PAI-BP learning media integrated with maritime values was developed using the ADDIE model and underwent three validation stages involving media experts, design experts, PAI teachers, and students through individual trials, small group trials, and field trials. The impact of the learning media product on enhancing learning motivation was determined through the product moment Pearson correlation test, yielding a calculated value of 0.838. This output resulted in a coefficient of determination (R Square) of 0.703, indicating that there is a 70.3% influence of using the learning media product on students' learning motivation, demonstrating a strong effect.